Comparison of Catalytic Activity of Copper Nanostructures in Friedel-crafts Type Condensation Reactions - Alireza Khorshidi (Science Faculty of Chiang Mai University, 2019)
The catalytic activity of copper nanostructures in the condensation reaction of selected indoles and aldehydes was investigated. Cu(acac)2, zeolite Y-encapsulated Cu(acac)2, free and zeolite Y-encapsulated CuO nanoparticles, and Cu2O nanoparticles were prepared successfully and characterized by means of UV-Vis spectroscopy, Fourier-transform infrared spectroscopy (FTIR), diffuse reflectance spectroscopy (DRS), X-Ray diffraction analysis (XRD), scanning electron microscopy (SEM), and energy dispersive X-Ray analysis (EDX). Cu2O nanoparticles showed superior activity as a heterogeneous catalyst compared to other catalytic systems. Excellent yields of the desired bis(indolyl)methanes were obtained via condensation reaction of indoles and aldehydes in presence of Cu2O nanoparticles under mild reaction conditions and the catalyst retained activity for six successive catalytic runs.